Dipolar Relaxation Dynamics at the Active Site of an ATPase Regulated by Membrane Lateral Pressure. (27th December 2016) - Fischermeier, Elisabeth; Pospíšil, Petr; Sayed, Ahmed; Hof, Martin; Solioz, Marc; Fahmy, Karim
Abstract: The active transport of ions across biological membranes requires their hydration shell to interact with the interior of membrane proteins. However, the influence of the external lipid phase on internal dielectric dynamics is hard to access by experiment. Using the octahelical transmembrane architecture of the copper‐transporting P1B ‐type ATPase from Legionella pneumophila as a model structure, we have established the site‐specific labeling of internal cysteines with a polarity‐sensitive fluorophore. This enabled dipolar relaxation studies in a solubilized form of the protein and in its lipid‐embedded state in nanodiscs. Time‐dependent fluorescence shifts revealed the site‐specific hydration and dipole mobility around the conserved ion‐binding motif. The spatial distribution of both features is shaped significantly and independently of each other by membrane lateral pressure. Abstract : Die Transmembranarchitektur der P1B ‐ATPase aus Legionella pneumophila wurde als Modellstruktur genutzt, um die positionsspezifische Markierung von nativen internen Cysteinen mit einem polaritätsempfindlichen Fluorophor zu etablieren. Dies ermöglichte dipolare Relaxationsstudien von solubilisierten und in Nanodiscs integrierten Formen des Proteins. Zeitabhängige Fluoreszenzverschiebungen zeigten die positionsspezifische Hydratation und Dipolmobilität in der Umgebung des konservierten ionenbindenden Motivs auf.